Pengaruh Risiko Likuiditas Terhadap Profitabilitas pada Perbankan Syariah dan Konvensional Di Indonesia - Nugraheni, Peni; Alam, Whinda Febrianti Iskandar (Universitas Muhammadiyah Yogyakarta, Indonesia, 2014)
This research aims to test the influence of liquidity risk to profitability in the Sharia and Conventional Banking empirically, and also to compare the existence of liquidity risk and profitability in the Sharia and Conventional Banking. Financing to Deposit Ratio (FDR), Liquid Asset to Deposit (LAD), and Liquid asset to Total Asset (LTA) as the proxy of liquidity risk. Profitability was proxied by Return on Asset (ROA). The results show that in Sharia Banking, FDR and LTA influence profitability positively and significanly, while the LAD influence negatively to the profitability. In the Conventional Banking, LTA variable effects negative and significant to the profitability and for the FDR and LAD have not significant effect on profitability. The research also finds that variables of FDR and LTA in Conventional and Sharia banking have significant differences, while LAD and ROA in Conventional and Sharia Banking have not significant differences.